1995
DOI: 10.1111/j.1834-7819.1995.tb04814.x
|View full text |Cite
|
Sign up to set email alerts
|

Major maxillofacial infections. An evaluation of 107 cases

Abstract: A review of 107 cases of acute maxillofacial infections managed at the Royal Melbourne Hospital was undertaken, and details of the presentations, demography, management, and outcomes of these patients are presented. The results indicated that many of the patients had sought treatment from dentists in general practice, and that a significant proportion had received sub-optimal management prior to referral. Thus a review of the principles of management and guidelines for the referral of patients with maxillofaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 38 publications
4
51
1
Order By: Relevance
“…In general, these findings were similar to other large Australian series in which 56 pulpal or pericoronal causes were treated in 57 months. 5 Comparison of the two studies, which were performed a decade apart, supports the anecdotal view that severe odontogenic infections are on the increase. The inclusion criteria were similar but the Melbourne series had 56 as compared to 48 cases gathered from a much larger population of 3.5 million (Melbourne) to 1.1 million (Adelaide).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In general, these findings were similar to other large Australian series in which 56 pulpal or pericoronal causes were treated in 57 months. 5 Comparison of the two studies, which were performed a decade apart, supports the anecdotal view that severe odontogenic infections are on the increase. The inclusion criteria were similar but the Melbourne series had 56 as compared to 48 cases gathered from a much larger population of 3.5 million (Melbourne) to 1.1 million (Adelaide).…”
Section: Discussionmentioning
confidence: 72%
“…Most patients have had multiple warning signs and symptoms prior to the onset of symptoms. Bridgeman et al 5 in their study of 107 Australian patients seen over a 57 month period found that all (100 per cent) of the patients had experienced pain prior to presentation. Commonly this had been intermittent and the patient had failed to act or obtained inadequate primary treatment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations